A modern jurisprudential analysis of how gender change affects marriage contracts, inheritance, and testimon - Hamed Al-Zahrani, Jumah (Journal of Social Sciences and Humanities, 2024)
Praise be to God who created the rules, judged what he created, and sent his Prophet Muhammad, may God's blessings and peace be upon him. God also judged among the people based on what he heard . To continue... Especially in the midst of the scientific revolution in the field of medicine and surgical experiments that are alien to our Muslim society, such as popular transformation, which It has taken on a wide debating, one of the most dangerous influences on the individual is what Western civilization produces of manifestations and behavior that have worked for our Muslim societies to undermine the values and morals of society, obliterate religious identity, and empower the Muslim. In order to demonstrate one aspect of the creative work's effectiveness about marriage and inheritance, Geneva has streamlined the testimony from the confines of intricacy and verbosity. The study began with a thorough explanation of its implications, followed by a discussion of the social change's driving forces, a discussion of the jurists' perspectives on the matter, a discussion of the study's methodology with regard to marriage, inheritance, and martyrdom, and a summary of its most important findings and recommendations. I pray to God for the study's success and reward .